Implementasi Metode Demonstrasi dalam Meningkatkan Keterampilan Siswa pada Materi Pengurusan Jenazah: Studi Kualitatif Naturalistik di SMK DASTAMACO Bekasi - Hajar Rifada Muzid; Agus Supriyanto (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2016)
Methods demonstration comes from the concept that learning should be student center learning, and learning should be fun, so they are motivated to continue to learn on their own without orders and feel overwhelmed and scared. To that end, the fun aspect of learning is becoming one of the important aspects in learning demonstration method, in addition to the efforts to continue to motivate their students to student exploration, creation, and continued to experiment in learning. The purpose of this study to determine and analyze the implementation of the demonstration method in improving students 'skills in handling materials in SMK Dastamaco Bekasi and to identify and analyze the factors inhibiting and supporting the implementation of demonstration method in improving students' skills in handling material bodies in SMK Dastamaco. Benefits of this research is to increase knowledge about the demonstration method in improving students' skills in handling material bodies in SMK Dastamaco. The results of this study can be concluded that the implementation of the demonstration method in improving students' skills in handling material bodies is quite good, with indicators that students can demonstrate their own way of handling the bodies properly.